Revisiting Psychiatric Social Work Practice in the Philippines: An Autoethnographic Case - Meneses, Alain Matteo (Asean Social Work Journal, 2024)
Over the past decades, there has been a gap in literature discussing the field of psychiatric social work in the Philippines. In an attempt to address this, this article describes a case to revisit the practice of psychiatric social work in the Philippine setting. Using an autoethnographic methodology, I recount my experience as a psychiatric social worker at a teaching hospital located in Quezon City, Metro Manila, Philippines, to illustrate the position, its roles and functions, and the common strategies it employs in practice. In discussing my personal experience, I reflect on themes and assert that psychiatric social work remains to have a continuing significance in today’s mental health landscape, offering innovative practices in response to newer challenges of helping patients with mental health conditions